SUMO modification of the ubiquitin-conjugating enzyme E2-25K - Pichler, Andrea; Knipscheer, Puck; Oberhofer, Edith; van Dijk, Willem J.; Körner, Roman; Olsen, Jesper Velgaard; Jentsch, Stefan; Melchior, Frauke; Sixma, Titia K. (Nature structural & molecular biology, 2005)
Post-translational modification with small ubiquitin-related modifier (SUMO) alters the function of many proteins, but the molecular mechanisms and consequences of this modification are still poorly defined. During a screen for novel SUMO1 targets, we identified the ubiquitin-conjugating enzyme E2-25K (Hip2). SUMO attachment severely impairs E2-25K ubiquitin thioester and unanchored ubiquitin chain formation in vitro. Crystal structures of E2-25K(1-155) and of the E2-25K(1-155)-SUMO conjugate (E2-25K*SUMO) indicate that SUMO attachment interferes with E1 interaction through its location on the N-terminal helix. The SUMO acceptor site in E2-25K, Lys14, does not conform to the consensus site found in most SUMO targets (ΨKXE), and functions only in the context of an α-helix. In contrast, adjacent SUMO consensus sites are modified only when in unstructured peptides. The demonstration that secondary structure elements are part of SUMO attachment signals could contribute to a better prediction of SUMO targets.